The Weighted Exponentiated Inverted Weibull Distribution: Properties and Application - Saghira, Aamir; Tazeema, Sadaf; Ahmad, Ishfaq (Journal of Informatics and Mathematical Sciences, 2017)
The weighted distributions are widely utilized in numerous real life fields such as medicine, ecology, reliability, etc., for the assibilation of proper statistical model. This paper innovates and studies a new three parameter Weighted Exponentiated Inverted Weibull Distribution (WEIWD). The mathematical properties of the suggested distribution including the cumulative distribution function, the moment generating function and the survival function are studied. The maximum likelihood estimation (MLE) method is implemented to estimate the proposed distribution parameters. Various candidate distributions are fitted on a data set of distance between crakes in a pipe. The result indicates that the WEIWD is the best fitted model for modeling of the real data set among the compared models.